Design and Immunological Validation of Macaca fascicularis Papillomavirus Type 3 Based Vaccine Candidates in Outbred Mice: Basis for Future Testing of a Therapeutic Papillomavirus Vaccine in NHPs - Neckermann, Patrick; Boilesen, Ditte Rahbaek; Willert, Torsten; Pertl, Cordula; Schrödel, Silke; Thirion, Christian; Asbach, Benedikt; Holst, Peter Johannes; Wagner, Ralf (Frontiers in Immunology, 2021)
Persistent human papillomavirus (HPV) infections are causative for cervical neoplasia and carcinomas. Despite the availability of prophylactic vaccines, morbidity and mortality induced by HPV are still too high. Thus, an efficient therapy, such as a therapeutic vaccine, is urgently required. Herein, we describe the development and validation of Macaca fascicularis papillomavirus type 3 (MfPV3) antigens delivered via nucleic-acid and adenoviral vectors in outbred mouse models. Ten artificially fused polypeptides comprising early viral regulatory proteins were designed and optionally linked to the T cell adjuvant MHC-II-associated invariant chain. Transfected HEK293 cells and A549 cells transduced with recombinant adenoviruses expressing the same panel of artificial antigens proved proper and comparable expression, respectively. Immunization of outbred CD1 and OF1 mice led to CD8+ and CD4+ T cell responses against MfPV3 antigens after DNA- and adenoviral vector delivery. Moreover, in vivo cytotoxicity of vaccine-induced CD8+ T cells was demonstrated in BALB/c mice by quantifying specific killing of transferred peptide-pulsed syngeneic target cells. The use of the invariant chain as T cell adjuvant enhanced the T cell responses regarding cytotoxicity and in vitro analysis suggested an accelerated turnover of the antigens as causative. Notably, the fusion-polypeptide elicited the same level of T-cell responses as administration of the antigens individually, suggesting no loss of immunogenicity by fusing multiple proteins in one vaccine construct. These data support further development of the vaccine candidates in a follow up efficacy study in persistently infected Macaca fascicularis monkeys to assess their potential to eliminate pre-malignant papillomavirus infections, eventually instructing the design of an analogous therapeutic HPV vaccine.